DESAIN PENGEMBANGAN MATERI AJAR BAHASA INDONESIA BERWAWASAN KESEHATAN DI SEKOLAH DASAR PADA MASA PANDEMI COVID-19 - Jannah Ulfah; Aninditya Sri Nugraheni (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2020)
This research is motivated by the outbreak of COVID-19. Maintaining health during the pandemic COVID-19  is very important. The purpose of this study is to provide health insights so that students understand the health protocol to prevent COVID-19. The approach used in this study is qualitative. The research method used is library research. Data analysis techniques in this study were data reduction, data presentation, concluding, and data verification. Amid the pandemic COVID-19, learning done online, so that the creativity of the teacher is very much needed so that students remain enthusiastic and motivated to follow the learning process despite the distance. The results of this study indicate that developing teaching materials with health insight is very important especially in Indonesian teaching materials so that students understand the importance of maintaining hygiene and health. So that students follow the health protocol and implement methods of prevention of COVID-19 transmission by diligently washing hands with soap, using masks, keeping a distance, and eating nutritious foods to avoid transmission and breaking the chain of spread of the virus.